FROM HUMAN RESOURCE TO HUMAN REAL SOURCE (Spiritual Management Perspective) - Reza Arfiansyah (State Islamic University of North Sumatra Indonesia, 2019)
Humans are God's creation, while science comes from human thought. One example of science is management science. There have been many management theories that have been delivered in a timely manner by management experts, such as the Theory of Human Resources (HR), Human Resource Management (HRM), and Strategic Human Resource Management (MSDMS). We have been busy discussing the management, but forgot about the study of man (human). For this reason, the relationship between man-management-money is inseparable, especially the man. The study of